Targeting men to improve maternal and child health and nutrition: A qualitative process evaluation of a mass media campaign in Tanzania’s Lake Zone - Dotto Kezakubi; Pieter Remes; Vianney Atugonza; Rosemary Kayanda; Abbie Clare; Ada Humphrey; Joanna Murray; Roy Head (PLoS ONE, 2026)
Background Undernutrition in the 1000 days following conception can cause lasting damage. In Tanzania malnutrition is directly or indirectly responsible for 35% of all deaths among children under five. The ASTUTE project, delivered in the five Lake Zone regions of Tanzania (Mwanza, Shinyanga, Geita, Kagera, Kigoma), aimed to reduce the prevalence of child stunting by improving child and maternal nutrition practices. The project incorporated a mass media campaign designed to change behaviours, with a particular emphasis on shifting gender norms and engaging men. Objective This paper focuses on the qualitative findings relating to the impact of the campaign on men’s knowledge, attitudes, norms and behaviours. Methods Throughout the period of radio and TV broadcasting, a qualitative process evaluation was conducted to assess the impact of the campaign on knowledge, attitudes, norms and behaviours. Between October 2017 and February 2020, a total of 59 focus group discussions were conducted with mothers, fathers and elder caregivers of a child aged under two years. Data were analyzed thematically. Results Fathers reported that radio and TV spots increased their participation in maternal health by accompanying their partners to the ANC, supporting their nutrition intake, and reducing the workload of the mother during pregnancy. Radio and TV spots were also reported to increase men’s engagement in child health by encouraging exclusive breastfeeding and nutritious complementary feeding. Conclusion Mass media campaigns that target men’s behaviour can have beneficial effects on maternal and child health. In particular, radio and TV messages targeting men appear to be able to mitigate some barriers arising from gender norms and women’s social position in Tanzania.